A cluster of acute-onset postoperative endophthalmitis over a 1-month period: investigation of an outbreak caused by uncommon species. Issue 4 (23rd August 2010) - Akçakaya, Aylin Ardagil; Sargın, Fatma; Erbil, Hasan Hasbi; Yazıcı, Saadet; Yaylalı, Sevil Arı; Mesçi, Cem; Ergin, Sevgi; Midilli, Kenan
Abstract : Aim: To report the clinical course, treatment response and prognosis of eight cases which developed acute-onset postoperative endophthalmitis over a 1-month period. Methods: 8 patients who were operated on over a period of 1 month and developed acute postoperative endophthalmitis were evaluated. Five of the patients had cataract surgery, one had cataract surgery combined with silicone extraction, and two patients had pars plana vitrectomy (PPV). Clinical patterns were observed, intraocular cultures were obtained, and the source of the organisms causing the epidemic was investigated. All patients had intravitreal antibiotic injections, three had PPV, and in two patients anterior chamber irrigation was performed. Results: Vitreous cultures showed Cellulosimicrobium cellulans in three cases and Stenotrophomonas maltophilia in one case. Four of the cases were culture negative. Stenotrophomonas maltophilia were also isolated from unused bottles of irrigating solutions. The final visual acuity of the patients ranged between HM and 7/10. All three patients with Cellulosimicrobium cellulans had a final visual acuity of ≥5/10. The available irrigating solutions were changed, and the endophthalmitis did not recur. Conclusions: The authors are unaware of any previous reports of postoperative endophthalmitis associated with Cellulosimicrobium cellulans. Prompt management with microbiological support, intravitreal antibiotics and PPV when needed were the key to good visual outcomes in this endophthalmitis outbreak.